Application of cooperative learning model type stad to increase student learning in these thermochemical - Fauziah Fauziah (Jurnal Pendidikan Kimia (JPKim), 2017)
This study aims to determine whether the application of STAD cooperative learning model is effectively used in improving students learning mastery, and how the students chemistry learning mastery on thermo-chemical subject after application of STAD cooperative learning model. This research is a Classroom Action Research.The results of research proved that the application of STAD cooperative learning model effectively used in improving students' chemistry learning mastery on thermo-chemical subject. Average learning outcomes of students in the first cycle of 74.49 with the completeness level of learning results of 82.05% (not completed in a classical), after the learning cycle II of the test results obtained learning average student learning outcome of 80.38 with a mastery level of student learning outcomes of 100% (completed thoroughly in classical). Student learning activities during learning from cycle I to cycle II by applying STAD cooperative learning model has increased. Thus, the results of this study are expected teachers especially chemistry teachers do collaborative work in the PTK as a vehicle for the development of professionalism of teachers in learning and it's time to use innovative learning, such as STAD type cooperative learning model.Key words: student learning mastery, cooperative learning model type STAD, PTK